Social Media Application For Coffee Shop Development In Bandung City - M Rafid; I Nyoman Tri Sutaguna; Arief Yanto Rukmana; Rusydi Fauzan; Muhammad Yusuf (IAIN Palopo, 2023)
MSMEs are self-sustaining, productive economic operations carried out by people or company organizations that are not subsidiaries in order to reap profits. MSMEs Coffee Shops in Bandung had to fight to innovate items in order to survive the pandemic. The purpose of this research is to investigate the impact of social media, innovation, and training on the development of coffee shop micro, small, and medium enterprises in Bandung. The research question is: Is there any influence of social media, innovation, and training variables on business development, both partially and simultaneously. The goal and benefits of this are to understand the partial and simultaneous impacts of the independent factors on the independent variables. The sample size for this study was 96 people.